2021
DOI: 10.1007/s10826-021-01941-3
|View full text |Cite
|
Sign up to set email alerts
|

Family Adaptability and Cohesion Evaluation Scale – Version IV (FACES IV): Validation Study in the Portuguese Population

Abstract: The present study addresses the psychometric properties of the Portuguese translation and adaptation of the Family Adaptability and Cohesion Evaluation Scale -version IV (FACES IV). The sample included 1089 individuals from 387 nuclear families, with an average age of 36 years. Besides its sociodemographic heterogeneity, the sample also included participants in various stages of the family life cycle and belonging to different family subsystems. We found overall good to moderate psychometric properties, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Communication serves to facilitate the relative levels of cohesion and adaptability within families. Communication within families could have an effect on their adaptability and cohesion (Kaewkerd et al, 2020; Sequeira et al, 2021). The current study focuses on the cohesion of families, which is one of the key constructs suggested by the Circumplex Model.…”
Section: Introductionmentioning
confidence: 99%
“…Communication serves to facilitate the relative levels of cohesion and adaptability within families. Communication within families could have an effect on their adaptability and cohesion (Kaewkerd et al, 2020; Sequeira et al, 2021). The current study focuses on the cohesion of families, which is one of the key constructs suggested by the Circumplex Model.…”
Section: Introductionmentioning
confidence: 99%